Stereoselective binding of propranolol in the elderly. - Colangelo, P (1989)
The influence of age on the stereoselective serum protein binding of propranolol was investigated. Serum was obtained from 10 young (mean age 23 +/- 2 years) and ten elderly (mean age 68 +/- 2 years) healthy male volunteers. The free fraction of propranolol (fu) was measured by equilibrium dialysis, using tritium labeled (+/-)- and (-)-propranolol. The fu values were 0.159 +/- 0.049 and 0.148 +/- 0.028 (+/-), 0.135 +/- 0.041 and 0.136 +/- 0.04 (-), 0.174 +/- 0.056 and 0.161 +/- 0.028 (+) in the young and elderly subjects, respectively. Serum alpha 1-acid glycoprotein (AAG) concentrations were 81.4 +/- 33.0 and 81.0 +/- 21.6 mg 100 ml-1 in young and elderly respectively (P greater than 0.05). Variability in AAG concentration accounted for most of the observed intersubject variability in the binding of both propranolol isomers. The stereoselective binding of propranolol does not appear to be affected by age.